2020
DOI: 10.1038/s41467-020-18884-w
|View full text |Cite|
|
Sign up to set email alerts
|

The structure of a red-shifted photosystem I reveals a red site in the core antenna

Abstract: Photosystem I coordinates more than 90 chlorophylls in its core antenna while achieving near perfect quantum efficiency. Low energy chlorophylls (also known as red chlorophylls) residing in the antenna are important for energy transfer dynamics and yield, however, their precise location remained elusive. Here, we construct a chimeric Photosystem I complex in Synechocystis PCC 6803 that shows enhanced absorption in the red spectral region. We combine Cryo-EM and spectroscopy to determine the structure−function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…is not the longest-wavelength form but emits at 713 nm in the trimeric PSI. The same three sites have been recently assigned as red Chls in Synechocystis PCC 6803 absorbing at 706, 707 and 714 nm [24,62]. We tentatively set the same absorption wavelengths (see Supplementary table S4), which resulted in an excellent fit of the experimental 77 K absorption and emission spectra (Supplementary Figure S8).…”
Section: Theoretical Modelling Of the Excitation Dynamicsmentioning
confidence: 78%
See 2 more Smart Citations
“…is not the longest-wavelength form but emits at 713 nm in the trimeric PSI. The same three sites have been recently assigned as red Chls in Synechocystis PCC 6803 absorbing at 706, 707 and 714 nm [24,62]. We tentatively set the same absorption wavelengths (see Supplementary table S4), which resulted in an excellent fit of the experimental 77 K absorption and emission spectra (Supplementary Figure S8).…”
Section: Theoretical Modelling Of the Excitation Dynamicsmentioning
confidence: 78%
“…The lowest-energy states emitting at 722-724 nm remain to be located on one or more Chls outside the monomerization region, e.g. A38/A39, B31/B32, B37/B38 [23][24][25]54].…”
Section: Red Chls In Trimeric Psimentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). In a very recent study, a chimeric Synechocystis PCC 6803 PSI into which the lumenal PsaB loop supporting the outer staircase chlorophyll B1233 was introduced has been characterized by both cryo-EM and spectroscopy 21 . The cryo-EM based atomic model showed that an additional chlorophyll corresponding to B1233 is present in the chimeric PSI complex and is causing a red shift.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, with a notable exception of the PSI monomer structure from Synechocystis sp. PCC 6803 solved at 4.0 Å resolution by X-ray crystallography 14 , all structures of cyanobacterial PSI have been determined from trimeric complexes 8,[15][16][17][18][19][20][21] or the recently discovered tetrameric PSI from Anabaena sp. PCC 7120 [22][23][24] and Chroococcidiopsis sp.…”
mentioning
confidence: 99%